(untitled) (The Journal of Plant Protection Sciences, 2020)
Cashew is one of the major significant sources of foreign currency for our country and it is also one ofthe important crops of Konkan region of Maharashtra State. Nearly 60 different pests have been reported on cashew. Among them the Tea Mosquito Bug, Helopeltis antonii Sign. is the most serious one, which is responsible for considerable yield losses in cashew. A field trial was conducted during 2005 at Cashew Research Farm, Regional Fruit Research station, Vengurle, Dist. Sindhudurg, (M.S.)with an objective to identify an alternative insecticide for management of Tea Mosquito Bug relative to the recommended spray schedule. The results indicated that out of six treatments selected, the treatment of 0.003% lambda-cyhalothrin was observed significantly superior over all other treatments